Las significaciones de la estética corporal en el programa “Combate”. - Narváez Naranjo, Rómel Ariel (2018)
The following research work has been set as a primary objective, to identify which are the meanings of body aesthetics promoted in "Combat", also ensuring that this work will be proposed to demonstrate the behaviors and behaviors that young people adopt as a way of constructing meaning. Wanting to demonstrate the dominance exercised by the media and in particular the competition programs in today's society. Theoretically the influence of television will be studied from the perspective of a socializing element between the subject and its context, this form of interaction can contribute and endow the individual with experiences, or in some way represent characteristic features of a society. From Barbero's vision, we can understand the creation and significance of meanings related to television discourse. This dissertation has been approached from two approaches, one of them the quantitative where the survey was used as a technique, it allowed to know the opinions and positions of the respondents. The qualitative part will be in charge of a focus group that will discuss about the same points treated in the surveys. It was determined that most students have seen the program, but not all assimilate it in a constructive way, they discover attitudes and behaviors that are commonly tacit. Keywords: meanings, body aesthetics, contest programs, media, construction of meaning.